2018
DOI: 10.1017/s1744133117000469
|View full text |Cite
|
Sign up to set email alerts
|

A successful Charter challenge to medicare? Policy options for Canadian provincial governments

Abstract: In September 2016, a case went to trial in British Columbia that seeks to test the constitutionality of provincial laws that (1) ban private health insurance for medically necessary hospital and physician services; (2) ban extra-billing (physicians cannot charge patients more than the public tariff); and (3) require physicians to work solely for the public system or 'opt-out' and practice privately. All provinces have similar laws that have been passed to meet the requirements of federal legislation, the Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A major constitutional challenge in British Columbia (BC) alleges that the restrictive CHA and provincial legislation infringe on patients' rights to life, liberty and security of the person under the Canadian Charter of Rights and Freedoms ( Flood and Thomas 2018 ). The arguments before the BC Supreme Court asserted that patients should have the right to obtain medical services more quickly by paying privately, and physicians should be allowed to "extra bill" patients for these services in the public system while also being permitted to "dual practice," working both in the public and an exclusively privately funded system.…”
Section: Medicare's Challenges and The Call For Private Financingmentioning
confidence: 99%
“…A major constitutional challenge in British Columbia (BC) alleges that the restrictive CHA and provincial legislation infringe on patients' rights to life, liberty and security of the person under the Canadian Charter of Rights and Freedoms ( Flood and Thomas 2018 ). The arguments before the BC Supreme Court asserted that patients should have the right to obtain medical services more quickly by paying privately, and physicians should be allowed to "extra bill" patients for these services in the public system while also being permitted to "dual practice," working both in the public and an exclusively privately funded system.…”
Section: Medicare's Challenges and The Call For Private Financingmentioning
confidence: 99%
“…In particular, anti-Medicare forces have advocated for the elimination of uniform coverage to allow for the right to access private insurance and private services along with the introduction of user fees will be necessary to address the perceived shortcomings of Canadian Medicare (Bliss, 2010;Blomqvist & Busby, 2015;Speer & Lee, 2016). Increasingly, arguments against single-tier Medicare and the underlying contending values are presented to the courts in cases where plaintiffs argue that the provincial laws and regulations that protect the single-tier aspect of provincial Medicare systems are contrary to individual rights as defined under the Charter of Rights and Freedoms in the Canadian Constitution (Flood & Thomas, 2018).…”
Section: Health Carementioning
confidence: 99%
“…That Charter rights could be used to undermine medicare is a grave rebuke to the assumption, common among advocates of human rights and dignity, that rights litigation is a positive, progressive force. As Flood and Thomas (2018) discuss in this volume, these Charter challenges will serve either as a wakeup call or death knell for medicare; everything depends on how Canadian governments respond. The courts can permit privatization to undercut equity and access, or they can respond creatively with new legal and policy solutions to improve equity and access, defending the human rights and dignity of all.…”
mentioning
confidence: 99%
“…Gaps in coverage persist, and have significant consequences for Canadians’ health. For example, a 2012 study found that roughly 5000 deaths and up to 2700 heart attacks and strokes could have been prevented among younger and middle-aged diabetes patients in Ontario, over the six-year period studied, if the province had a universal drug plan and these individuals were able to access insulin and other needed medications (Booth et al ., 2012).…”
mentioning
confidence: 99%